Bidirectional Translations Between Observational and Topography‐Based Hydrographic Data Sets: MERIT‐Basins and the SWOT River Database (SWORD) - Jeffrey Wade; Cédric H. David; Elizabeth H. Altenau; Elyssa L. Collins; Hind Oubanas; Stephen Coss; Arnaud Cerbelaud; Manu Tom; Michael Durand; Tamlin M. Pavelsky (Water Resources Research)
Abstract The recently launched Surface Water and Ocean Topography (SWOT) Mission is expected to provide transformative observations of water surface elevation, width, and slope and produce derived estimates of discharge for global rivers along rivers in the SWOT River Database (SWORD). However, the hydrographic representation of rivers in SWORD differs from hydrography data sets commonly used for modeling purposes, such as Multi‐Error‐Removed Improved Terrain (MERIT)‐Basins. Here, we develop links between the river networks of SWORD and MERIT‐Basins (MB) to enable interoperability between SWOT data products and hydrologic modeling frameworks. This data set, termed MERIT‐SWORD, identifies a subset of ∼277,000 global MB river reaches that most closely represent the location and extent of the SWORD river network and establishes bidirectional, one‐to‐many translations between reaches in the two hydrographic data sets. The MERIT‐SWORD data set serves to unite SWOT observations with river routing models, allowing for the seamless and standardized assimilation of SWOT vector products into global river simulations and the provision of improved a priori discharge estimates for SWOT discharge computation.